2002
DOI: 10.1038/nmat772
|View full text |Cite
|
Sign up to set email alerts
|

Long-range structuring of nanoparticles by mimicry of a cholesteric liquid crystal

Abstract: Patterning nano-objects is an exciting interdisciplinary research area in current materials science, arising from new optical and optoelectronic properties and the need to miniaturize electronic components. Many techniques have been developed for assembling nanoparticles into two- and three-dimensional arrays. Most studies involving liquid crystals as templates have dealt with colloidal particles and nematic and smectic phases. Here, we demonstrate the long-range ordering of nanoparticle assemblies that adopt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
128
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(140 citation statements)
references
References 19 publications
8
128
0
4
Order By: Relevance
“…This is not straightforward to explain, however it does not seem to be connected to the oxidation state of the particles in the composite since the transition temperatures remains unchanged if the sample is left exposed to the air during three months. Earlier studies have demonstrated a destabilization of the mesophases in physical mixtures of liquid crystal and inorganic nanoparticles, which was attributed to chemisorption effects [20]. On the other hand, a recent example showed that fluxional ligands can provide a certain degree of freedom which allows the LC to preferentially organize itself around the nanoparticles and to improve the LC properties [21].…”
Section: Mesomorphous Behavior Of the Liquid Crystal Polymer Compositesmentioning
confidence: 99%
“…This is not straightforward to explain, however it does not seem to be connected to the oxidation state of the particles in the composite since the transition temperatures remains unchanged if the sample is left exposed to the air during three months. Earlier studies have demonstrated a destabilization of the mesophases in physical mixtures of liquid crystal and inorganic nanoparticles, which was attributed to chemisorption effects [20]. On the other hand, a recent example showed that fluxional ligands can provide a certain degree of freedom which allows the LC to preferentially organize itself around the nanoparticles and to improve the LC properties [21].…”
Section: Mesomorphous Behavior Of the Liquid Crystal Polymer Compositesmentioning
confidence: 99%
“…Periodic soft materials with spontaneous breaking of translation symmetry such as block copolymers (lamellar, cylindrical, cubic and gyroid phases) [1][2][3] and liquid crystals (smectic, cholesteric and columnar phases) [4][5][6][7][8][9][10] are being actively investigated for creating self-assembled ordered structures and templates for micro and nanoscale applications. Periodic soft materials may help overcome the limits of current microfabrication techniques in terms of easiness, rapidity, cost and spatial resolution, with the added benefi t of a large response to external stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] The incorporation of various nanomaterials into liquid crystals (LCs), and the complexity of their interaction, have recently attracted much interest. [3][4][5][6][7][8][9][10][11][12] The addition of nanoparticles (NPs) to liquid crystals produces composite materials with additional functionality, and tunable optic, electric, magnetic, or electrooptic properties. Both molecular and macroscopic bulk properties are modifi ed.…”
mentioning
confidence: 99%